TRADE CONCENTRATION VS. DIVERSIFICATION: A STUDY OF CHINA AND INDIA (2001-2023) - Manisha Devi; Sharma, Lalit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The primary objective of this study is to analyze trade relations between China and India. It utilizes indicators such as the trade intensity index, concentration index, and diversification index to assess their trade dynamics. The analysis is based on secondary data from WITS and UN Comtrade, covering the period from 2001 to 2023. The findings indicate that China has a highly diversified export structure, allowing it to adapt to global economic changes, whereas India’s exports remain concentrated in a limited number of industries. Despite efforts to enhance trade relations, the study highlights India’s continued structural dependence on Chinese imports as a key economic challenge.